If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 + 6r = -8r + -6(1 + -1r) -22 + 6r = -8r + (1 * -6 + -1r * -6) -22 + 6r = -8r + (-6 + 6r) Reorder the terms: -22 + 6r = -6 + -8r + 6r Combine like terms: -8r + 6r = -2r -22 + 6r = -6 + -2r Solving -22 + 6r = -6 + -2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2r' to each side of the equation. -22 + 6r + 2r = -6 + -2r + 2r Combine like terms: 6r + 2r = 8r -22 + 8r = -6 + -2r + 2r Combine like terms: -2r + 2r = 0 -22 + 8r = -6 + 0 -22 + 8r = -6 Add '22' to each side of the equation. -22 + 22 + 8r = -6 + 22 Combine like terms: -22 + 22 = 0 0 + 8r = -6 + 22 8r = -6 + 22 Combine like terms: -6 + 22 = 16 8r = 16 Divide each side by '8'. r = 2 Simplifying r = 2
| 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 | | 9/7(M-19) | | -2x+3=5x-2 | | 7x^9/8-35=0 | | -7(3)+13= | | 2178=p(1+.03*7) | | 10y=72+y | | 2/3-(5/6) | | 4x+5y-28=0 |